Ethics, identity and ideology: A study of the interpreters in the War of Resistance against Japanese Aggression (1937–1945) - Li, Ping; Tian, Chuanmao; Huang, Zhonglian (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
In this article we explore interpreter ethics in China’s War of Resistance against Japanese Aggression (1937–1945). Interpreter ethics in conflict zones may be divided into professional and situation ethics, and situation ethics is the focus of this study. Apart from professional identity and ideology, interpreters have other identities and ideologies such as national identity and political ideology, especially when they belong to either of the conflicting parties. The concepts of ethics, identity and ideology remain unchanged when they are related to interpreting as a profession. However, they have different connotations when they are associated with a nation, a group or a community. As mediators across languages and cultures, interpreters are more likely to face moral crises in wartime than in peacetime. Therefore, in many cases, they have to violate professional ethics in order to follow situation ethics, and situation ethics varies with their identities and ideologies. The research findings show that during the War of Resistance against Japanese Aggression, interpreters’ national identity remained the same but their moral attitude changed.